Defect characterization in optical coatings using scattered light - Loglia, Balthazar; Derrick, Emma; Ingraham, Luke; Fraser, Alexandra; Geng, Yutong; Sanger-Johnson, Grace; Colby, Kace; Kontos, Antonios (Applied optics. Optical technology and biomedical optics, 2023)
Optical coatings play a vital role in sensing technologies. The development of new coatings that exhibit minimal optical losses requires a detailed understanding of the development of defects within them. Current methods of defect characterization involve direct microscope imaging or x-ray diffraction studies in the case of crystallites. In this paper, we demonstrate the characterization of coating defects using light scattering, which can yield information about their size, location, and index of refraction. The method requires measuring the scattered power of each individual defect as a function of angle and comparing the data with theoretical models. Finally, we argue that this method can be used for the determination of the defect location within a multi-layer stack.Optical coatings play a vital role in sensing technologies. The development of new coatings that exhibit minimal optical losses requires a detailed understanding of the development of defects within them. Current methods of defect characterization involve direct microscope imaging or x-ray diffraction studies in the case of crystallites. In this paper, we demonstrate the characterization of coating defects using light scattering, which can yield information about their size, location, and index of refraction. The method requires measuring the scattered power of each individual defect as a function of angle and comparing the data with theoretical models. Finally, we argue that this method can be used for the determination of the defect location within a multi-layer stack.